Eksplorasi Keanekaragaman Filum Arthropoda Permukaan Tanah Menggunakan Pitfall Trap di Desa Jaboi, Kecamatan Sukajaya, Kota Sabang - Khansa Ruqayya; Maulida Adzkia; Ismaturrahmi Ismaturrahmi; Fajarna Humaira; Ahlul Mursyidi (Universitas Syiah Kuala, 2025)
Ground arthropods are a group of animals whose life cycle occurs partly or entirely above the ground, so they can be used as environmental bioindicators, especially to determine soil quality. The higher the diversity of ground arthropods in an area, the better the soil quality. This study aims to explore the diversity of the ground arthropod phylum in Jaboi Village, Sukajaya District, Sabang City, using the pitfall trap method. Jaboi Village is an active volcanic area with fertile soil and supports the life of various species. Sampling was carried out at four points using containers filled with detergent as insect traps. The captured specimens were identified to the species level and analyzed using the Shannon-Wiener diversity index. The results showed that 9 families were found with a diversity index value of H' = 2.36, which is categorized as moderate diversity. The dominant species include Acheta domesticus, Velarifictorus micado, and Camponotus modoc. This diversity reflects the stability of the ecosystem and the good environmental quality in the area. This study emphasizes the importance of managing and monitoring arthropod diversity as bioindicators in environmental conservation efforts. highlights the importance of sustainable management and regular monitoring of Arthropod diversity as bioindicators in environmental conservation efforts.